Business incubators in China: an inquiry into the variables associated with incubatee success - Haiyang Zhang; Tetsushi Sonobe (Kiel Institute for the World Economy (IfW), 2010)
This paper examines the association between the outcome of business incubation and the resources used by incubators, by using a small panel of science and technology business incubators (STBIs) in China. We find that while the number of firms graduating from an STBI is closely correlated with the infrastructure as well as the human and financial resources at the STBI's disposal, the graduates' firm sizes, in terms of employment and value added, as well as their labor productivity are unrelated to such resource inputs. We also find that the educational levels of incubator managers and the financial support given to their clients have significant impacts on the number of graduates. However, the number of graduates does not increase with the scale and diversity of the cities in which their STBIs are located or with the presence of foreign ventures and universities in the locality. We do not find that university-based and government-established STBIs differ significantly in their incubation performance.
Keywords: M13; O31; O32; O38; 330; business incubators; new firms; market failures; government policy; human resources; China; Unternehmensgründung; Technologie; Industrielle Forschung; Erfolgsfaktor; Infrastruktur; Humankapital; Finanzierung; Wirtschaftsförderung; Schätzung; China